Application of Solar Energy-Based Pest Control Tools to Improve the Quality of Rice Plants to Reduce Farmer Losses - Frida, Erna; Ferry Rahmat A. Bukit; Suherman; Syiska Yana; Bunga Fisikanta Bukit (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2025)
Rice is one of the most important staple crops in Indonesia. Rice is the main source of food for the majority of Indonesia's population, including the Stabat area, which is a small town part of Langkat Regency, North Sumatra Province. Rice itself needs water to grow and develop, and is a plant that is no stranger to pests in the form of birds, mice, javelin, and so on. In dealing with pests, farmers in Stabat usually still use traditional methods by installing scarecrows and using pesticides to kill the pests. The work carried out by always going to the fields takes up a lot of energy and time from farmers. The University of North Sumatra Community Service Team offers a solution, namely making tools to protect rice plants from pests (javelin, aphids, caterpillars, mice, fungi) using pest detection sensors to help farmers in caring for rice to maintain the quality and quantity of rice through spraying pests to reduce losses incurred by farmers, especially during the harvest period. Solar energy-based pest control tool to improve the quality of rice plants to reduce losses. Farmers can also reduce the spraying of rice pests using chemicals so that soil fertility is maintained